Rapid screening of Musa species for resistance to black leaf streak using in vitro plantlets in tubes and detached leaves - Twizeyimana, M.; Ojiambo, P.S.; Tenkouano, A.; Ikotun, T.; Bandyopadhyay, Ranajit (Scientific Societies, 2007)
This study investigated the utility of inoculation of in vitro plantlets in tubes and detached leaves as reliable and rapid assays for screening Musa genotypes against Mycosphaerella fijiensis, the causal agent of black leaf streak. In the first part of the study, three types of inocula were evaluated to determine suitability for in vitro inoculation. Inoculation of in vitro plantlets with mycelial fragments resulted in significantly (P< 0.05) higher levels of disease severity and faster rates of disease progress compared with inoculations using conidial suspensions. In the detached leaf assay, amending agar medium with plant hormones significantly (P< 0.0001) aided retention of green leaf color. Leaf pieces on medium containing gibberellic acid at 5mgliter had about 5% chlorosis at 52 days after plating. When in vitro plantlets in tubes and detached leaves of 10 Musa genotypes with different levels of disease resistance were inoculated with M. fijiensis, there were significant (P< 0.05) differences among genotypes in leaf area infected, incubation time, and symptom evolution time. For incubation time and leaf area infected, cultivars responded depending on their level of disease resistance, with resistant genotypes Calcutta-4 and PITA-17 having significantly (P= 0.001) longer incubation times and lower infected leaf areas compared with the susceptible cultivar Agbagba and moderately resistant cultivar FHIA-23. A similar pattern in cultivar response was observed for symptom evolution time. Leaf area infected was not significantly (P= 0.2817 for two-tailed t test) different when assessed using the two assays, and infected leaf areas in both assays were strongly correlated (r= 0.88, n= 48, P<0.0001). Although incubation times were significantly (P= 0.0062 for two-tailed ttest) different between the two assays, values from the two assays were strongly correlated (r= 0.69, n= 48, P< 0.0001). These results show that these two assays are rapid and space-effective, and can reliably be used for screening Musa genotypes for resistance to black leaf streak.